Pemikiran Filosofis M.Athiyah Al-Abrasyi (Religius-Rasional) dan Relevansinya dengan Pendidikan Islam Kontemporer - Riza Febriansyah; Muh. Asharif Suleman; Anan Marliansyah; Kurnia Utami Nursholichah; Ushie Uswatun Hasanah (Reflection : Islamic Education Journal, 2024)
Muhammad Athiyah Al-Abrasyi is a leading educator and thinker in the world of Islamic education. Al-Abrasyi devoted his life to developing the concept of integral and comprehensive education. This paper discusses Muhammad Athiyah Al-Abrasyi and gains a deeper understanding of his thoughts on contemporary Islamic education today. The following research applies qualitative and literature research methods as the main source, utilizes reference sources from various journals and books that are in line with this discussion, and uses descriptive analysis in analyzing it. In addition, this research focuses on the analysis of the thoughts, contributions, and works of a famous figure in a certain field. The results of this paper conclude that according to him, the main purpose of education is to form individuals who are of character and moral, well-rounded, and able to contribute positively to society. His ideas were very influential among Muslim educators and continue to be relevant today. al-Abrasyi's emphasis on the integration between religious and general sciences has made him an important figure in the ongoing educational discourse, inspiring many educational institutions to implement a holistic approach in their curricula.